Foxp3‐mediated inhibition of Akt inhibits Glut1 (glucose transporter 1) expression in human T regulatory cells. Issue 2 (9th December 2014) - Basu, Samik; Hubbard, Britany; Shevach, Ethan M.
Abstract : Elucidation of the molecular mechanisms behind differentialGlut1 expression in human conventional and regulatory T cells. Abstract : CD4 + CD25 + Foxp3 + Tregs have a diminished capacity to activate the PI3K/Akt pathway. Although blunted Akt activity is necessary to maintain Treg function, the consequences of this altered signaling are unclear. Glut1 is a cell‐surface receptor responsible for facilitating glucose transport across plasma membranes, whose expression is tightly coupled to costimulatory signals and Akt phosphorylation. Freshly isolated human Tregs were unable to up‐regulate Glut1 in response to TCR and costimulatory signals compared with Tconv . Consequently, the ability of Tregs to use glucose was also reduced. Introduction of Foxp3 into Tconv inhibited Akt activation and Glut1 expression, indicating that Foxp3 can regulate Glut1. Finally, pharmacologic activation of Akt in Tregs can induce Glut1, overcoming the effects of Foxp3. Together, these results illustrate the molecular basis behind differential glucose metabolism in Tregs .